A history of Israelite religion in the Old Testament period - Albertz, Rainer (Louisville John Knox Press, 1994)
This book, the second of two volumes, offers a comprehensive history of Israelite religion. It is a part of the Old Testament Library series.
Keywords: Judaism -- History -- To 70 A.D. Bible. -- Old Testament -- Theology. Jews -- History -- To 70 A.D.